Incidence and predictors of mortality among neonates admitted with perinatal asphyxia at west Oromia tertiary hospitals, Ethiopia, 2022 - Dawit Tesfaye Daka; Chalachew Adugna Wubneh; Tewodros Getaneh Alemu; Bewuketu Terefe (BMC, 2023)
Abstract Background Perinatal asphyxia is one of the preventable and treatable causes of neonatal mortality. However, it is the fifth-largest cause of under-five mortality. Even with management advancements, it remains one of the key public health issues in underdeveloped countries, including Ethiopia. Comorbidities are also understated; therefore, adequate information regarding the incidence of death and its predictors is required. Methods A four-year retrospective follow-up study was conducted from October 3 to November 2, 2022. From a total sample size, of 655, 616 data were collected by nurse through follow-up reviews charts using Kobo Toolbox software. The data was exported to STATA Version 14 for analysis. The Cox proportional hazard assumption was checked, and the model for the data was selected using Akaike Information Criteria. Finally, an adjusted hazard ratio with 95% CI was computed, and variables with a P-value < 0.05 in the multivariable analysis were taken as significant predictors of death. Result The overall incidence of mortality was 38.86/1000 (95% CI: 33.85-44.60). The median time of follow-up was 15 days (95% CI: 14-20). The proportion of deaths was 202 (32.79%, 95% CI: 29.18-36.61) among neonates with perinatal asphyxia. While the distance from health facility > 10 km is (AHR: 2.25; 95% CI: 1.60-3.17), direct oxygen (AHR: 1.83; 95% CI: 1.35-2.48), APGAR score (Appearance, Pulse, Grimace, Activity, and Respiration) < 3 at the fifth minute (AHR: 2.63; 95% CI: 1.03-6.73), prolonged rupture of membrane (AHR: 1.41; 95% CI: 1.02-1.94), and stage III hypoxic ischemic encephalopathy (AHR: 2.02; 95% CI: 1.18-3.47) were predictors of mortality among neonates with perinatal asphyxia. Conclusion According to this study's findings, high neonatal mortality due to perinatal asphyxia requires proper intervention regarding membrane rupture, APGAR score (Appearance, Pulse, Grimace, Activity, and Respiration), oxygen use, stage III hypoxic-ischemic encephalopathy, and residence distance.